2020
DOI: 10.1186/s12870-020-02685-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and metabolomic profiling reveals the effect of LED light quality on morphological traits, and phenylpropanoid-derived compounds accumulation in Sarcandra glabra seedlings

Abstract: Background Sarcandra glabra is an evergreen and traditional Chinese herb with anti-oxidant, anti-bacterial, anti-inflammatory, and anti-tumor effects. Light is one of the most influential factor affecting the growth and quality of herbs. In recent times, the introduction of Light Emission Diode (LED) technology has been widely used for plants in greenhouse. However, the impact of such lights on plant growth and the regulatory mechanism of phenylpropanoid-derived compounds in S. glabra remain un… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…In earlier research, we observed that RL considerably increased plant height and decreased stem diameter and leaf area, while BL significantly reduced plant height and leaf area of S. glabra. Meanwhile, the BL substantially reduced the production of esculetin, caffeic acid, isofraxidin, and fraxidin, but accumulated the contents of quercitrin and kaempferol in leaves of S. glabra [16]. Under RL irradiation, the contents of cryptochlorogenic acid, cinnamic acid, and kaempferol significantly decreased in leaves of S. glabra [16].…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In earlier research, we observed that RL considerably increased plant height and decreased stem diameter and leaf area, while BL significantly reduced plant height and leaf area of S. glabra. Meanwhile, the BL substantially reduced the production of esculetin, caffeic acid, isofraxidin, and fraxidin, but accumulated the contents of quercitrin and kaempferol in leaves of S. glabra [16]. Under RL irradiation, the contents of cryptochlorogenic acid, cinnamic acid, and kaempferol significantly decreased in leaves of S. glabra [16].…”
Section: Introductionmentioning
confidence: 94%
“…Meanwhile, the BL substantially reduced the production of esculetin, caffeic acid, isofraxidin, and fraxidin, but accumulated the contents of quercitrin and kaempferol in leaves of S. glabra [16]. Under RL irradiation, the contents of cryptochlorogenic acid, cinnamic acid, and kaempferol significantly decreased in leaves of S. glabra [16].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The secondary metabolism of plants shows sensitivity toward the quality and quantity of applied light (Danziger and Bernstein, 2021). Red, white, blue, and blue-violet light differentially affect genes, enzymes, intermediates, and products of the phenylpropanoid pathway (Taulavuori et al, 2018;Xie et al, 2020). Drought stress may also affect genes and enzymes of the phenylpropanoid pathway (Li et al, 2020).…”
Section: Phenolic Profilementioning
confidence: 99%